Building the information system of the French Critical Zone Observatories network: Theia/OZCAR-IS. Issue 16 (10th December 2022) - Braud, Isabelle; Chaffard, Véronique; Coussot, Charly; Galle, Sylvie; Juen, Patrick; Alexandre, Hugues; Baillion, Philippe; Battais, Annick; Boudevillain, Brice; Branger, Flora; Brissebrat, Guillaume; Cailletaud, Rémi; et al.
ABSTRACT: The French Critical Zone research infrastructure, OZCAR-RI, gathers 20 observatories sampling various compartments of the critical zone, each having developed their own data management and distribution systems. A common information system (Theia/OZCAR IS) was built to make their in situ observation FAIR (findable, accessible, interoperable, reusable). The IS architecture was designed after consultation of the users, data producers and IT teams involved in data management. A common data model based on various metadata standards was defined to create information fluxes between observatories' ISs and the Theia/OZCAR IS. Controlled vocabularies were defined to develop a data discovery web portal offering a faceted search with various criteria, including variables names and categories that were harmonized in a thesaurus published on the web. This paper describes the IS architecture, the pivot data model and open-source solutions used to implement data discovery, and future steps to implement data downloading and interoperability services.